Optimization of friction surfaced deposits of aluminium alloy 6068 over low carbon steel. (2022) - Ravi Sekhar, S.; Raju, M.; Govardhan, D.; Karthikeyan, R.; Sravan Sashank, S.
Abstract: Friction surfacing is a surface modification process by using friction. All the researchers and industrialist are concentrating in this area as there are no fumes and spark is involved during the process, can be automated and regulated easily. Hence all conventional process can be replaced. The studies were carried out to create a friction coating on the surface of a low carbon steel substrate using aluminium alloy 6068 and friction surfacing. The effects of three parameters on width and height were determined: frictional pressure, mechtrode speed in rpm, and welding transverse speed. The defect free friction deposited surfaces were confirmed through visual, metallurgical and bend test. Out of these three factors welding speed was found the most dominating factor. The linear regressions were established for the two responses viz. deposited width and deposited height. To optimize the responses Taguchi's three factors and two level designs was used.